Analisis Pengendalian Persediaan Bahan Baku Dengan Metode Just In Time Pada PT. Aneka Adhilogam - Solid Widiastuti; Indah Wahyu Utami; Garnet Filemon Waluyo (Jurnal Rekayasa Proses dan Industri Terapan, 2023)
Inventory management is one of the efforts to maintain the operational continuity of a company. This study aims to determine the most optimal raw material inventory control using the Just in Time (JIT) method for research objects at PT. Aneka Adhilogam Karya in Klaten Regency which produces various pipe fittings. Data collection through direct interviews, observation and literature study. The results of this study showed that the JIT method was able to make inventory costs as efficient as Rp. 1,429,297 with the original cost of Rp. 2,468,087 to Rp. 1,038,790. Another result of this study states that the frequency of purchases using the Just in Time method is more efficient than company policy.